Foreign Direct Investment and SME Development: Some Policy Issues for Transition and Developing Countries (UNWE Yearbook, 2008)
The paper is concerned with one of the ways of contributing to strengthening the indigenous SME sector in a situation of resource scarcity. Specifically, the paper is concerned with the potential role of foreign direct investment (FDI) in relation to the long-term competitive development and internationalization of the SME sector in transition and developing countries. Whilst this is not a new topic, a number of recent trends suggest there may be greater scope for developing such linkages in the future than in the past.These include the emergence of new sources of FDI in developing and emerging economies themselves; increasing signs of SMEs internationalizing their operations rather than simply exporting from their domestic base, as well as a continued increase in outsourcing by MNEs. Whilst such trends undoubtedly present challenges to SMEs in transition and developing countries, they also present opportunities.More specifically, the paper aims to contribute to the development of policies that can help to strengthen the SME sector in developing and transition economies, through promoting their integration into, and potential benefits from, the global economy. This involves firstly, policies to increase the attractiveness of transition and developing economies for foreign investors, who are willing and able to contribute (indirectly) to the strengthening of the capacity of the SME sector in these countries; and secondly, policies designed to strengthen the benefits of foreign investment to local economies through the facilitation of SME trade and investment linkages and building the capacity of local SMEs to take advantage of new market opportunities created. The challenge for governments in all countries is to create a facilitating and supportive environment for SME development that enables SMEs to exploit the potential benefits arising from increasing internationalization, whilst avoiding becoming protective or intervening in ways that displace, distort or crowd out market solutions and, ideally, helping to contribute to building market capacity.The paper represents a review of existing literature and case material, rather than being based on original empirical evidence. Following the introduction, the rest of the paper is divided into two main sections and a conclusion. Section 2 reviews recent trends in FDI; the potential benefits of developing FDI-SME linkages, together with an assessment of the evidence of such relationships in practice. Section 3 considers the main policy implications of the analysis, paying attention to policy making in different contexts, including public policy makers in mature market economies as well as in developing and transition economies; but also business policy makers in FDI enterprises and SMEs in a developing/transition economy context.